1980
DOI: 10.1029/ja085ia01p00055
|View full text |Cite
|
Sign up to set email alerts
|

Electric fields, electron precipitation, and VLF radiation during a simultaneous magnetospheric substorm and atmospheric thunderstorm

Abstract: A balloon payload instrumented with a double‐probe electric field detector and an X ray scintillation counter was launched from Roberval, Quebec, Canada (L =4.1) at 0828 UT (0328 LT) on July 9, 1975. A magnetospheric substorm was observed locally between 0815 and 1100 UT, which produced a maximum ΔB of ∼500 nT at ∼0930 UT. A single‐cell atmospheric thunderstorm developed northeast of Roberval beginning around 0925 UT which was most intense from ∼1000 to 1035 UT. Detailed study of the electrical properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(25 citation statements)
references
References 35 publications
4
21
0
Order By: Relevance
“…On most of the flights the conductivity measurements were obtained by the relaxation time method (Mozer and Serlin, 1969, Benbrook et al, 1974, Bering et al, 1980, Holzworth, 1981, Rosen et al, 1982, Holzworth et al, 1986, Norville and Holzworth, 1987. Various types of probes were used on the flights.…”
Section: Instrumentationmentioning
confidence: 99%
See 1 more Smart Citation
“…On most of the flights the conductivity measurements were obtained by the relaxation time method (Mozer and Serlin, 1969, Benbrook et al, 1974, Bering et al, 1980, Holzworth, 1981, Rosen et al, 1982, Holzworth et al, 1986, Norville and Holzworth, 1987. Various types of probes were used on the flights.…”
Section: Instrumentationmentioning
confidence: 99%
“…The balloon flights were conducted during many separate balloon campaigns, some by our groups and others taken from the literature : 1973, and 19991975 at Roberval, Quebec;1980-1981at Siple Station, Antarctica, 1985at South Pole, 1990-2003from Syowa Station, Antarctica, 1999at Ottumwa, Iowa, 1983-84 and 1992 from Christchurch, New Zealand, six flights from 1986 to 1994 from Hyderabad, India, and several flights from 1978, 1979, and 1983 from Laramie, Wyoming (Paltridge, 1965;Benbrook et al, 1974;Morita and Ishikawa, 1976;Widdell et al, 1976;Rosen et al, 1978Rosen et al, , 1982Rosen et al, , 1985Bering et al, 1980Bering et al, , 1987Bering et al, , 2003Bering et al, , 2005Holzworth, 1981Holzworth, , 1991Rosen and Hofmann, 1981;Holzworth et al, 1984Holzworth et al, , 1986Holzworth et al, , 2005Gupta and Narayan, 1987;Norville and Holzworth, 1987;Byrne et al, 1990Byrne et al, , 1991Udare et al, 1991;Gupta et al, 1992;Ejiri et al, 1995;Ebihara et al, 1996;Chakravarty et al, 1997;Gupta, 2000Gupta, , 2004. The locations of the...…”
Section: Introductionmentioning
confidence: 99%
“…Measurements of conductivity above storms using the relaxation technique from a constant level balloon platform, however, have found contradictory results (e.g. Bering et al 1980;Holzworth et al 1986;Pinto et al 1988;Hu et al 1989;Saba et al 1999). For example Holzworth et al (1986) flew a double Langmuirprobe, measuring bipolar conductivities from super pressure balloons at altitudes of 26km over thunderstorms.…”
Section: Conductivity Above Thunderstormsmentioning
confidence: 99%
“…Measurements of electric current and fields in the lower atmosphere show variations associated with solar flares (Cobb, 1967;Muhleisen, 1971;Holzworth and Mozer, 1979;Michnowski, 1998;Tinsley, 2000), solar magnetic sector boundary crossings (Markson, 1971, Park, 1976, geomagnetic activity (Cobb, 1967;Marcz, 1976;Tanaka et al, 1977;Bering et al, 1980), auroral activity (Freier, 1961;Olson, 1971;Lobodin and Paramonov, 1972;Shaw and Hunsucker, 1977), and solar cycle variations (Muhleisen, 1977;Olson, 1977;Tinsley, 2000). A specific mechanism for the solar terrestrial coupling through atmospheric electricity has been suggested and studied (Markson, 1971(Markson, , 1978Markson and Muir, 1980;Roble, 1985;Lakhina, 1993;Rycroft et al, 2000).…”
Section: Introductionmentioning
confidence: 97%